Magnetic–Plasmonic Nanoassemblies: Core–Shell‐Heterostructured Magnetic–Plasmonic Nanoassemblies with Highly Retained Magnetic–Plasmonic Activities for Ultrasensitive Bioanalysis in Complex Matrix (Adv. Sci. 2/2020). Issue 2 (22nd January 2020) - Hao, Liangwen; Leng, Yuankui; Zeng, Lifeng; Chen, Xirui; Chen, Jing; Duan, Hong; Huang, Xiaolin; Xiong, Yonghua; Chen, Xiaoyuan
Abstract : In article number 1902433, Xiaolin Huang, Yonghua Xiong, and co‐authors report the facile synthesis of magnetic–plasmonic nanoassemblies (MPNAs) which exhibit a typical core–shell structure, wherein oleylamine‐coated gold nanoparticles (OA‐AuNPs) preferentially aggregate and form a plasmonic core and oleic acid‐coated iron oxide nanoparticles (OC‐IONPs) assemble a magnetic shell. The resultant MPNAs hold the highly retained magnetic–plasmonic activities for the separation and simultaneous optical sensing of target compounds in complex biological samples.